Clinical features and treatment outcomes in children with IgG subclass deficiency: A retrospective study - Sahin, Filiz Demir; Kapcay, Ozan; Kilic, Mehmet (Codon Publications, 2025)
Introduction: Immunoglobulin G (IgG) subclass deficiencies are among the most common primary immunodeficiencies in children and are associated with increased susceptibility to infections. This study aimed to investigate the clinical features, associated immunological conditions, and treatment outcomes in affected pediatric patients. Methods: A retrospective analysis was conducted on 43 patients diagnosed with IgG subclass deficiency at the Allergy and Immunology Clinic of F & imath;rat University between January 2019 and July 2024. Clinical records were reviewed for demographic data, immunoglobulin levels, and history of infections. The impact of prophylactic treatments-including intravenous immunoglobulin (IVIG), oral bacterial lysates, and antibiotics-on the frequency of infection was evaluated. Results: Among the 43 patients, 32 (74.4%) were male and 11 (25.6%) were female, with a mean age at diagnosis of 6.77 +/- 2.30 years. The most common clinical presentation was recurrent upper respiratory tract infections, reported in 23 patients (53.5%). Isolated IgG3 deficiency was identified in 34 patients (79.1%). During follow-up, normalization of IgG levels was achieved in 39 patients (90.7%), with a mean time to normalization of 2.1 +/- 1.19 years. Prophylactic interventions significantly reduced the annual infection rate from 18.12 +/- 10.37 to 3.09 +/- 2.40 (p < 0.001). Conclusion: IgG subclass deficiencies represent a significant health concern in children because of their association with recurrent infections. Early diagnosis and the implementation of appropriate prophylactic treatment strategies are crucial in reducing infection frequency and improving the quality of life. However, the retrospective nature of the study and the relatively small sample size may have limited the evaluation of clinical outcomes and treatment responses, potentially affecting the generalizability of the results. Despite these limitations, the findings highlight the potential benefits of prophylactic interventions in managing infections among children with IgG subclass deficiencies and emphasize the need for larger, prospective studies to inform evidence-based therapeutic strategies for this population.
Keywords: IgG3 deficiency; recurrent infections; IgG subclass deficiency; IgG3 deficiency; immune profilaxis; immunoglobulin replacement therapy; recurrent infections